The Paddy Cropping Calendar Map In Tidal Swampland Field Of South Kalimantan - Nur wakhid; Haris Syahbuddin (Politeknik Negeri Batam, 2019)
Tidal swampland is one of sub optimal land that potential as a backup of fertile field in Java island. However, due to the global climate change, negatively impact the paddy production including the cropping time that shifted year by year. Therefore, the objective of this study was to develop a cropping calendar map of tidal swampland in three conditions, i.e. dry, normal, and wet years. This map was developed by analyzing the relationship between precipitation and tide overflow data. Also, primary data from field survey and farmer questionnaire were used for verification. The area was delineated by cropping calendar combined with administration, climate, tidal swampland, and rice field map. Using this map, the cropping time in tidal swampland field can be potentially increased become twice a year. By proper cropping time, the paddy production in tidal swampland of South Kalimantan also potentially will increased directly.